2000
DOI: 10.1088/0953-4075/33/20/306
|View full text |Cite
|
Sign up to set email alerts
|

Threshold electron impact ionization of carbon tetrafluoride, trifluoromethane, methane and propane

Abstract: We have studied the ionization behaviour close to threshold for the fragment ion production from CF 4 , CHF 3 , CH 4 and C 3 H 8 . In particular, we use a reliable method to extrapolate weak ion signals towards the appearance energy. Our evaluation is based on an extension of Wannier's law for the ionization of atoms towards the case of polyatomic molecules. In the experiment we use a hemispherical electron monochromator with an energy resolution of ≈135 meV. The vibrationally cold target molecules are prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 63 publications
6
61
0
4
Order By: Relevance
“…Comparison of the data with the zero-KER thresholds for CF 4 [37], and the synchrotron measurements on C 2 F 6 , C 3 F 8 , and C 3 F 6 measured by Jarvis et al [16,17], indicate that G4 theory underestimates the results from photoionization experiments by, at worst, around 3%. However, thresholds for CF 3 + , CF 2 + , and CF + measured in EI-ionization experiments on CF 4 can be significantly higher than the adiabatic values calculated via G4 theory by amounts up to several electron volts [55]. This is most probably a consequence of the fact that vertical excitation and impulsive dissociation often form cations at highly nonequilibrium geometries.…”
Section: Theoretical Methodsmentioning
confidence: 88%
“…Comparison of the data with the zero-KER thresholds for CF 4 [37], and the synchrotron measurements on C 2 F 6 , C 3 F 8 , and C 3 F 6 measured by Jarvis et al [16,17], indicate that G4 theory underestimates the results from photoionization experiments by, at worst, around 3%. However, thresholds for CF 3 + , CF 2 + , and CF + measured in EI-ionization experiments on CF 4 can be significantly higher than the adiabatic values calculated via G4 theory by amounts up to several electron volts [55]. This is most probably a consequence of the fact that vertical excitation and impulsive dissociation often form cations at highly nonequilibrium geometries.…”
Section: Theoretical Methodsmentioning
confidence: 88%
“…The parent ion CF 4 + is not observed due to its instability [37,39,48]. According to Stephan et al [46], Brehm et al [22] and Fiegele et al [50], the life time of CF 4 + ion is below 10 µs. On the other hand, some studies found indications of the existence of the CF 4 + ion with very small relative intensity [64][65][66][67].…”
Section: Fragment Ion Time Of Flight (Tof) Spectrum Of Cfmentioning
confidence: 99%
“…Electron impact studies include measurements on electron energy loss [33][34][35][36][37][38][39][40][41], excitation [42], ionization observing total [43,44], total dissociation [45] and partial ionization cross sections using fragment ion mass analysis [42,[46][47][48][49][50][51][52]. Furthermore, binary (e, 2e) studies [53,54] and electron impact fragment ion-photon coincidences (FIPCO) [55] were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, IE a s of halomethanes and radicals and AEs of ion fragments from halomethanes have been measured by electron impact ionization (EI) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], photoionization mass spectrometry (PIMS) or photoionization efficiency spectroscopy (PIES) , photoelectron spectroscopy (PE) [41][42][43][44][45][46][47][48][49][50][51][52][53], and (threshold) photoelectronphotoion coincidence (TPEPICO) techniques [54][55][56][57][58][59][60][61][62][63][64][65][66][67]. The early results, mainly from EI, PI, and PE studies, have been collected by NIST [68].…”
Section: Introductionmentioning
confidence: 99%